Memórias: o retrospecto de minha história educacional e uma breve reflexão de atuação profissional - PINHEIRO, Regina da Conceição Quaresma (2024)
This memorial was requested as a course completion work fron the Pedagogy course of the Federal University of Pará. The aim of this work is the register of my childhood memories, my school life, my teaching practice and my entrance in the upper course, reminding important moments from my personal and professional life. This work also aims to remind the knowledge construction process during the period of formation and learning as well the changes occurred in my pedagogical ideas.